SERS-based approaches toward genetic profiling. (January 2015) - De Silva Indrasekara, Agampodi Swarnapali; Fabris, Laura
In the last decade surface-enhanced Raman scattering (SERS) has experienced an important resurgence, and as a consequence it has seen wide application in the biological field, especially for DNA identification. SERS-based DNA detection can be carried out directly and indirectly and, in the latter approach, it relies on the use of SERS tags, whose role is to indirectly prove the recognition and binding of a specific oligonucleotide sequence. Herein, the role of SERS tags is analyzed focusing specifically on the use of DNA identification for genetic profiling.